Implementation of the Entrepreneurship Capability Improvement Program in the Tourism Sector in Manado City - Florence D. J. Lengkong; Joorie M. Ruru; Very Y. Londa (Newinera Publisher, 2022)
Tourism and entrepreneurship are related to strengthening the country's economy, income and community welfare. The growth of business actors in the tourism sector needs to continue to be improved in terms of quality and quantity. So various programs have been carried out by the government related to the implementation of programs to increase entrepreneurial abilities. Using a qualitative design, this research was conducted to examine the implementation of an entrepreneurial capacity building program in Manado City. Research findings show that the